The P2Y2 receptor mediates uptake of matrix-retained and aggregated low density lipoprotein in primary vascular smooth muscle cells. (September 2016) - Dissmore, Tixieanna; Seye, Cheikh I.; Medeiros, Denis M.; Weisman, Gary A.; Bardford, Barry; Mamedova, Laman
Abstract: Background and aims: The internalization of aggregated low-density lipoproteins (agLDL) mediated by low-density lipoprotein receptor related protein (LRP1) may involve the actin cytoskeleton in ways that differ from the endocytosis of soluble LDL by the LDL receptor (LDLR). This study aims to define novel mechanisms of agLDL uptake through modulation of the actin cytoskeleton, to identify molecular targets involved in foam cell formation in vascular smooth muscle cells (VSMCs). The critical observation that formed the basis for these studies is that under pathophysiological conditions, nucleotide release from blood-derived and vascular cells activates SMC P2Y2 receptors (P2Y2 Rs) leading to rearrangement of the actin cytoskeleton and cell motility. Therefore, we tested the hypothesis that P2Y2 R activation mediates agLDL uptake by VSMCs. Methods: Primary VSMCs were isolated from aortas of wild type (WT) C57BL/6 and. P2Y2R−/− mice to investigate whether P2Y2 R activation modulates LRP1 expression. Cells were transiently transfected with cDNA encoding a hemagglutinin-tagged (HA-tagged) WT P2Y2 R, or a mutant P2Y2 R that unlike the WT P2Y2 R does not bind the cytoskeletal actin-binding protein filamin-A (FLN-A). Results: P2Y2 R activation significantly increased agLDL uptake, and LRP1 mRNA expression decreased in P2Y2R−/− VSMCs versus WT. SMCs, expressing P2Y2 R defective in FLN-A binding, exhibit 3-fold lower LDLR expression levels than SMCs expressing WT P2Y2 R, while cells transfected with WT P2Y2 R show greater agLDL uptake in both WT and P2Y2R−/− VSMCs versus cells transfected with the mutant P2Y2 R. Conclusions: Together, these results show that both LRP1 and LDLR expression and agLDL uptake are regulated by P2Y2 R in VSMCs, and that agLDL uptake due to P2Y2 R activation is dependent upon cytoskeletal reorganization mediated by P2Y2 R binding to FLN-A. Highlights: LRP1 is transcriptionally upregulated by UTP. P2Y2 R activation increased LRP1 expression and agLDL internalization.